Autochthonous cheeses of Bosnia and Herzegovina - Zlatan Sarić; Sonja Bijeljac (Mljekarstvo)
Despite the migration of people towards cities, autochthonous cheeses in Bosnia and Herzegovina survived. Technologies of these cheeses are simple and adapted to humble mountain limitations. Geographical occasions and rich mountain pastures created a certain participation of ewe's milk cheeses. Communicative isolation of hilly-mountain regions resulted in "closed" cheese production in small households. Autochthonous cheeses in Bosnia and Herzegovina have various origins. Different cheeses are produced in different parts of Bosnia and Herzegovina. There are : Travnički cheese, Masni (fat cheese), Presukača, Sirac, Livanjski cheese, Posni (lean cheese), "Suvi" (dry cheese) or "Mješinski" full fat cheese matured in sheepskin bag, fresh sour milk cheese "Kiseli" and dried sour milk cheese "Kiseli", Zajednica, Basa, Kalenderovački cheese and goat's milk cheeses (Hard and White soft goat's milk cheese), "Zarica" and Urda. Besides above-mentioned types of cheese in Bosnia and Herzegovina some other autochthonous dairy products are produced: Kajmak (Cream), Maslo (Rendered butter) and Zimsko kiselo mlijeko (Winter sour milk). The specificity in Bosnia and Herzegovina is that autochthonous dairy products are still mainly both produced and consumed in small rural households. Exceptions are Travnički cheese and Kajmak that are significantly sold at market. Only Livanjski cheese is manufactured as industry dairy product.